1986
DOI: 10.5479/si.00810266.58.1
|View full text |Cite
|
Sign up to set email alerts
|

Stratigraphic Record of the Neogene Globorotalid Radiation (Planktonic Foraminiferida)

Abstract: Cifelli, Richard, and George Scott. Stratigraphic Record of the Neogene Globorotalid Radiation (Planktonic Foraminiferida). Smithsonian Contribu¬ tions to Paleobiology, number 58, pages 101, 43 figures, 1986.-The histories of lineages forming the Neogene globorotalid radiation in the planktonic foraminifera are reconstructed primarily from stratigraphic distributions. Data on major taxa are synthesized, with particular reference to the devel¬ opment of shell design, and related to biogeograpy and evolutionary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 31 publications
0
30
0
Order By: Relevance
“…11 A, angiensis, Notorotalia wilsoni, Mucronina subtetragona, C), weakly convex spiral surfaces of late-formed chambers, Rectuvigerina ruatoria, and Textularia miozea. Rectoand the relatively compressed axial profile of the shell bolivina maoria appears in the upper Altonian Globorotalia (Cifelli & Scott 1986 (Fig. 11) results.…”
Section: Haeuslerella Pukeuriensismentioning
confidence: 99%
See 2 more Smart Citations
“…11 A, angiensis, Notorotalia wilsoni, Mucronina subtetragona, C), weakly convex spiral surfaces of late-formed chambers, Rectuvigerina ruatoria, and Textularia miozea. Rectoand the relatively compressed axial profile of the shell bolivina maoria appears in the upper Altonian Globorotalia (Cifelli & Scott 1986 (Fig. 11) results.…”
Section: Haeuslerella Pukeuriensismentioning
confidence: 99%
“…12A-H) RECOGNITION: Walters ( 1965) considered that the species evolved from Globorotalia incognita, an interpretation that has been adopted in several subsequent stratigraphic studies (reviewed by Cifelli & Scott 1986), and also shown in a cladistic analysis of some Neogene Globorotalia (Norris et al 1994). Scott et al (1990) suggested that the pattern of transformation was step-like, with architectural modifications occurring in a short stratigraphic interval.…”
Section: Paleobathymetrically Useful Benthic Foraminifera (Continued)mentioning
confidence: 99%
See 1 more Smart Citation
“…Highest occurrence of Fohsella peripheroronda Blow & Banner PHYLETIC STATUS: An early member (Blow & Banner 1966) of the F ohsella lineage which apparently persisted in the South Pacific temperate region after the demise of low-latitude populations (Cifelli & Scott 1986). The highest occurrence is interpreted as an extinction event.…”
Section: Lowest Occurrence Of Paragloborotalia Mayeri Cushman and Ellisormentioning
confidence: 99%
“…Highest occurrence of Globorotalia conica Jenkins PHYLETIC STATUS: The species has been reported mainly from the Australasian region; its origin is poorly known. Cifelli & Scott (1986) regarded it as the end member of the Globorotalia zealandica lineage. There are no descendants known and the highest occurrence is considered to represent its extinction, at least in the temperate province.…”
Section: Lowest Occurrence Of Paragloborotalia Mayeri Cushman and Ellisormentioning
confidence: 99%